TEACHER–STUDENT COLLABORATION: HOW ARTIFICIAL INTELLIGENCE IS CREATING A NEW ERA IN FOREIGN LANGUAGE EDUCATION - M.B. Mirzaraimova, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article explores the transformative influence of Artificial Intelligence (AI) on teacher–student collaboration in the field of foreign language education, examining how technological innovations reshape pedagogical interaction, learner autonomy, and instructional  methodology.  Through  a  critical  analysis  of  the  linguistic  relativity hypothesis, sociocultural learning theory, and communicative methodology, the study argues that AI creates a triadic model of collaboration among teacher, learner, and intelligent system.  The findings highlight the necessity of integrating AI within an ethical, linguocultural, and pedagogically balanced framework to ensure sustainable progress in language learning.